The effect of two passive head-down tilt positions on diaphragm excursion in healthy adults: A preliminary study. (2nd April 2016) - Schewitz, Jacqui; Roos, Ronel; van Aswegen, Heleen; Manda, Samuel
ABSTRACT: Background and Purpose : A head-down tilt position could influence diaphragm excursion due to abdominal content displacement. The purpose of the study was to determine if excursion could be influenced by a head-down tilt position and if this change in excursion alters the diaphragm function. Design : Prospective quasi-experimental study. Participants : Seventy healthy adult students. Intervention : Four head-down tilt positions: 1) 15° (30 seconds); 2) 15° (120 seconds); 3) 30° (30 seconds); and 4) 30° (120 seconds). Outcome Measures : Change in diaphragm excursion was assessed using M-Mode ultrasound and diaphragm function was recorded in terms of the peak expiratory flow rate (PEFR) and thoracic expansion. Data were analyzed using descriptive statistics, Analysis of Variance (ANOVA), Kruskal Wallis and student's t -test. Results : The cohort consisted of 56 women (80%) and 14 men (20%) with a mean age of 20.7 (±1.7) years and a mean body mass index (BMI) of 23.0 (±3.7) kg/m 2 . The greatest mean change in the hemi-diaphragm, for both genders measured from rest, was 38.8 (±11.5) mm on the left and 39.4 (±11.9) mm on the right. The greatest stretch occurred after a 30° head-down tilt for 30 seconds for both the right and left hemi-diaphragms in males and right hemi-diaphragm in females. The left hemi-diaphragm in females achieved its maximum stretch after 30° head-down tilt for 120 seconds. No significant changes in thoracic expansion or PEFR were observed but baseline values were less than predicted. Conclusion : Optimal change in hemi-diaphragm excursion was obtained utilizing 30° head-down tilt positions in healthy subjects.